If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 2y = -2.5 Solving 7x + 2y = -2.5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 7x + 2y + -2y = -2.5 + -2y Combine like terms: 2y + -2y = 0 7x + 0 = -2.5 + -2y 7x = -2.5 + -2y Divide each side by '7'. x = -0.3571428571 + -0.2857142857y Simplifying x = -0.3571428571 + -0.2857142857y
| 4x^4=9x^2 | | A=a+b-5 | | (3ab2c3)2/(ab)*(2a3b4) | | 5+3(4x+1)= | | 9x+3x=-3 | | 14lnx=20 | | 5n-12=108 | | 3(x^2-6)=129 | | -18=-6x-6 | | 4x+8=-2x+24 | | -7-6w+5+3= | | X^3lnx=0 | | x-.13x-58=75 | | 400=200+0.04s | | 7-9r+5r-8= | | 2(x-3)=3(x-2)+2 | | lnx^4=0 | | 3078x-4104=57(54x-72) | | 6m-2n=27 | | X/6-8=1 | | (3e+5f-7)+(4e-8f)= | | X^2-62=2x+1 | | F(x)=-2x^2+10x+48 | | -7(-3y+2)-4y=3(y-1)-5 | | -3(2x+8)=-66 | | x+4=7.8 | | 3(5x+4)=-5(2x-4) | | (-3/4)x(7/4) | | 9x+31x-10=8(5x+9) | | -5v+7=6(v+3) | | 2x-6=3x-6+2 | | 2(-6+5x+6xsquared)=0 |